The financial leverage paradox. The confusion surrounding the leverage concept - Berent, Tomasz S. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
With the help of a simple question juxtaposing geared and ungeared positions, this paper analyzes the inherent ambiguity present in the concept of financial leverage. The answer to this question depends on the way it is (often automatically) understood. It may be perceived as being either about risk, risk reward or a mix of the two. The range of possible answers is virtually unlimited. Unfortunately, most of them, including that given by Miller in his Nobel Prize Lecture, are inconsistent with finance theory. This paradox is represented by the inability to answer the simple question in an unambiguous way, yet its gravity comes from the fact that it is neither noted nor debated in the literature. The confusion surrounding financial performance evaluation, ROE debate or executive pay are just a few examples of how lethal the leverage paradox can be. The leverage-driven financial crisis of recent years shows that the chaos in the literature exemplified by the paradox may easily spill over into real life
Argumenta Oeconomica, 2020, Nr 1 (44), s. 301-319